Clinician and Patient Reporting of Symptomatic Adverse Events in Cancer Clinical Trials: Using CTCAE and PRO-CTCAE® to Provide Two Distinct and Complementary Perspectives - Minasian LM; O'Mara A; Mitchell SA (Patient Related Outcome Measures, 2022)
Lori M Minasian,1 Ann O’Mara,2,3 Sandra A Mitchell4 1Division of Cancer Prevention, National Cancer Institute, Bethesda, MD, USA; 2Consultant, ICF, Fairfax, VA, USA; 3Consultant to Division of Cancer Prevention, National Cancer Institute, Bethesda, MD, USA; 4Division of Cancer Control and Population Sciences, National Cancer Institute, Bethesda, MD, USACorrespondence: Lori M Minasian, Division of Cancer Prevention, National Cancer Institute, 9609 Medical Center Drive, 5E-342, MSC-9784, Bethesda, MD, 20892-9784, USA, Tel +11 240 276 7053, Fax +11 240 276 7846, Email minasilo@mail.nih.govAbstract: Inclusion of the patient perspective in the reporting of symptomatic adverse events provides different and complementary information to clinician reporting using the Common Terminology Criteria for Adverse Events (CTCAE). The National Cancer Institute’s Patient-Reported Outcomes version of the Common Terminology Criteria for Adverse Events (PRO-CTCAE®) is designed for patients to self-report their symptomatic adverse events in a manner that complements CTCAE reporting. Using CTCAE and PRO-CTCAE together offers the potential to refine our understanding of the prevalence and trajectory of lower grade AEs that can lead to elective discontinuation of therapy and diminished quality of life. This review addresses the development of PRO-CTCAE with an emphasis on the differences between PRO-CTCAE scores and CTCAE severity grades. This distinction is important when evaluating, grading and reporting toxicity and tolerability in cancer clinical trials.Keywords: Patient-Reported Outcomes version of the Common Terminology Criteria for Adverse Events, PRO-CTCAE, patient-reported outcomes, cancer therapy, toxicity, tolerability